ANALISIS PEMANFAATAN PRODUK PEMBIAYAAN PENSIUN PADA BANK SYARIAH DI INDONESIA - Artanoga, Fawwaz; Inayatillah, Inayatillah; Mulia, Rika (Jihbiz: Global Journal of Islamic Banking and Finance, 2024)
This research aims to determine the utilization of pension financing at Bank Syariah Indonesia (BSI) in Aceh Tengah, Aceh Province. This research uses descriptive qualitative research methods. Interviews was conducted to collect facts, data or material objects which are not in the form of a series of numbers, but rather expressions in the form of language or discourse (whatever the form) through appropriate and systematic interpretation. it can be concluded that the BSI financing mechanism for pensions at one of their branch  in Aceh Tengah has demonstrated that activities are carried out in accordance with the established mechanism. There are customers who use pension financing for both productive and consumptive purposes.